TUG OF WAR BETWEEN SUNNAH TASYRÎ’IYYAH AND GHAYR TASYRÎ’IYYAH: A CASE STUDY OF A HADÎTH REGARDING USE OF CAMEL URINE AS MEDICATION - Yusuf Hanafi (Jurnal Ushuluddin, 2019)
Qur’anic texts and Prophetic sunnah are essentially zamâniy and makâniy in nature. According to historical records, Muhammad Shallallâhu ‘alaihi wa sallam was playing numerous roles. Therefore, every Moslem really needs to associate sunnah with the status of the Prophet at the time a sunnah was delivered when attempting to understand and practice it. This study aims to discuss the instruction by the Prophet Muhammad, peace and blessings of Allah be upon him, for a group of companions to drink camel urine when they complained of sickness from the perspectives of sunnah tasrî’iyyah and sunnah ghayr tasyrî’iyyah. This study is a literature study using content analysis techniques. The results identified that the hadîth above is categorized as sunnah ghayr tasyrî’iyyah. The advice of the Prophet in the hadîth above to drink camel urine as a medicine must be understood in the emergency context with no medicine other than camel urine available. This is the opinion of the majority of Moslem scholars that taking medication with something that is najis is not permissible, except in a compelling emergency. Under a normal condition and in the presence of halal medicines, taking medication with something that is najis – like camel urine – is harâm